Modification of the Microstructure and Transport Properties of La2CuO4−δ Electrodes via Halogenation Routes - Dos-Santos-Gómez, Lucía; Zamudio-García, Javier; Porras-Vázquez, José Manuel; Ramírez-Losilla, Enrique; Marrero-López, David (IOAP-MPDI, 2022)
dos Santos-Gómez L, Zamudio-García J, Porras-Vázquez JM, R. Losilla E, Marrero-López D. Modification of the Microstructure and Transport Properties of La2CuO4−δ Electrodes via Halogenation Routes. Processes. 2022; 10(6):1206. https://doi.org/10.3390/pr10061206
Keywords: Halogenación; La2CuO4−δ; Ruddlesden–Popper; Anion doping; Solid oxide fuel cell; Halogenation